2021
DOI: 10.22146/jkap.59680
|View full text |Cite
|
Sign up to set email alerts
|

Performance Allowance, Motivation, Employees’ Work Achievement And Organizational Performance Among Goverment Employees

Abstract: This research analyzed the relationships among performance allowance, employee motivation, work achievement and organizational performance in the Ministry of Religion's Office Lumajang City. This research used a quantitative research design based on. Structural Equation Modeling (SEM) model. Research results showed insignificant direct between performance allowance and motivation, employees’ work achievement, and organizational performance. Work achievement has a direct and strongest significant influence on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Secondly, it is strongly suggested that the three antecedents of COE represented the portfolios of HRM. Aligned with the research of (Sunahwati, M., & Sukmawati, 2019), the research findings also stated that HRM is the most crucial antecedent of the organizational performance, besides motivation and achievement (Mudhofar & Gumanti, 2021b).…”
Section: Op (Organizational Performance)mentioning
confidence: 60%
See 1 more Smart Citation
“…Secondly, it is strongly suggested that the three antecedents of COE represented the portfolios of HRM. Aligned with the research of (Sunahwati, M., & Sukmawati, 2019), the research findings also stated that HRM is the most crucial antecedent of the organizational performance, besides motivation and achievement (Mudhofar & Gumanti, 2021b).…”
Section: Op (Organizational Performance)mentioning
confidence: 60%
“…Flat proposition from the model offered is the COE could be considered as the unique organizational capability and value creation, so is the organization characterized has a strong COE compared with the competitors. Moreover, the impact of work achievement on organizational performance (Mudhofar & Gumanti, 2021a) There are several reasons to propose that the COE will offer value creation for organization. Firstly, when employees interact with one another, the effect of spreading where the affective element, motivation, shared and collective behavioral within employees are increased, including the attributes for interrelated performance such as perceived or shared collective efficacy and high group potency (Bakker & Schaufeli, 2000).…”
Section: Evidence Of Coe On Organizational Performancesmentioning
confidence: 99%
“…For Mercer, this can result in personal change, team groups, and organizations. In the end, human resources are motivated to continue raising service levels (Mudhofar, 2021).…”
Section: Graph 2 Effectiveness Of Academic Services Of Administrative...mentioning
confidence: 99%